Optimization Pressure of Water Distribution Network System of the Banjarsari Water Treatment Plant, PDAM Bojonegoro - Utama, Teguh Taruna; Zumrotin, Amelia (LPPM Universitas Andalas, 2022)
The distribution network of the Banjarsari water treatment plant uses a gravity system. The system serves the drinking water in Banjarsari Villages. This study aims to optimize the pressure of the water distribution network in the Banjarsari Villages. This system supplies water from the Banjarsari water treatment plant. The water distribution network uses the gravity method to deliver water to customers. The drinking water distribution network was obtained from PDAM Bojonegoro. Meanwhile, the elevation and node of pipe were obtained by using Google Earth. Before optimization, the water distribution network has negative pressure at 07.00 AM and 05.00 PM. The negative pressure zone is at the end of the distribution network. The negative pressure values obtained using EPANET is range from -0,67 meters to -6,34 meters. The water distribution network is optimized by replacing diameter pipe in some areas, the water pressure increases significantly and makes the water distribution has positive pressure values. The pressure values are range from 2,70 meters to 13,65 meters. Replacing diameters of pipe is a solution to remove negative pressure, so that water from the reservoir can deliver to the end of a pipe. The distribution network pipe diameter is chosen which is close to the calculated pipe diameter.